Water regime shifts in the active soil layer of the Qinghai-Tibet Plateau permafrost region, under different levels of vegetation - Wang Genxu; Li Shengnan; Hu Hongchang; Li Yuanshou (Geoderma, 2009)
Soil moisture and water cycling in a permafrost active layer are affected in a synergistic manner by both the sequence of soil temperature and changes in vegetative cover. Between 2004 and 2007, the dynamics of soil water content and water movement in the active layer of alpine meadow soils were monitored at sites located in the permafrost region of the Qinghai-Tibetan Plateau, China for four years to examine the synergistic effects of freeze-thaw cycles and levels of vegetation cover. The analysis of variations in monthly and seasonal soil moisture, soil-desiccation index, and soil available indicated that soil moisture exhibited a relatively stable and consistent pattern over the growing season (July-September), independent from the vegetation cover. Greater soil moisture was present in the upper root zone and at the bottom of the soil profile, whereas lower moisture levels occurred in the middle portion of the profile. Irrespective of soil depth, the lower the vegetation cover, the quicker the increase in soil liquid water during the thaw initiation period (May and June), and the quicker its decrease during the freeze initiation period (October and November). In addition, the greater the vegetation cover, the greater the available water content of the upper root zone and the less the water content of the soil layer at 0.60-0.70 m depth below the root zone. Both the soil hydraulic parameters and the spatiotemporal distribution of the water content were subject to the synergistic action of the freeze-thaw cycle and the extent of vegetation cover. The variances in active soil heat transmission and heat-water coupling relationship under the different vegetation covers were considered the main driving factors in the distribution and dynamics of the active soil water regime. The permafrost supports the development of alpine frost meadow ecosystems, and well-ordered, high-cover alpine meadow vegetation favors the protection of permafrost from degradation. (C) 2009 Published by Elsevier B.V.